2020
DOI: 10.1044/2020_lshss-20-00001
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Multiple Auditory Processing Assessment–2: A Test of Auditory Processing Disorder

Abstract: Purpose A normative study using the Multiple Auditory Processing Assessment–2 (MAPA-2; Schow et al., 2018) was recently completed. With access to these data, the authors extend that work and support a definite construct for auditory processing disorder (APD). The goal here is to examine MAPA-2 reliability and validity (construct, content, and concurrent). Evidence for the APD construct is further buttressed by measures of sensitivity and specificity. Results of MAPA-2 testing on children diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…If the words comprise one digit in each ear, the task is very easy for most people, so the score obtained is usually very close to 100% for both ears, making it hard to detect small asymmetries. To “sensitize” the test, the task is made more difficult by sequentially presenting two digits, or even three digits ( Moncrieff & Wilson 2009 ; Schow et al 2020 ) to each ear before asking the listener to freely recall all the digits presented to both ears, or just those for a selected ear. Unfortunately, such a change makes the test more dependent on short-term memory and also on attention.…”
Section: Tests Versus Abilitiesmentioning
confidence: 99%
“…If the words comprise one digit in each ear, the task is very easy for most people, so the score obtained is usually very close to 100% for both ears, making it hard to detect small asymmetries. To “sensitize” the test, the task is made more difficult by sequentially presenting two digits, or even three digits ( Moncrieff & Wilson 2009 ; Schow et al 2020 ) to each ear before asking the listener to freely recall all the digits presented to both ears, or just those for a selected ear. Unfortunately, such a change makes the test more dependent on short-term memory and also on attention.…”
Section: Tests Versus Abilitiesmentioning
confidence: 99%
“…There are concerns that reference standards used for most current tests evaluating developmental APD do not fulfill these requirements (Vermiglio, 2018). Schow et al (2020) defines their reference standard as APD identified formally by local professionals using different methods and techniques. In this instance, the reference standards and the norms of tests used by the different professionals lacked clarity, and the reliability and validity of such an approach is questionable.…”
Section: Issue 3: Appropriateness Of Using Comorbidities As the Reference Standardmentioning
confidence: 99%
“…In this instance, the reference standards and the norms of tests used by the different professionals lacked clarity, and the reliability and validity of such an approach is questionable. Schow et al (2020Schow et al ( , p. 1001) also considered the rationale of using comorbidity as a reference standard. The authors themselves expressed concerns that their method was not ideal.…”
Section: Issue 3: Appropriateness Of Using Comorbidities As the Reference Standardmentioning
confidence: 99%
See 2 more Smart Citations